THE ROLE OF THE CHURCH IN THE CONSTRUCTION OF SYMBOLIC VIOLENCE AGAINST WOMEN IN CONTEMPORARY BRAZIL - Matheus Andrade Trajano Oliveira, Pablo; Alessandra Pacheco , Hevellen (Revista Gênero e Interdisciplinaridade, 2022)
This article seeks to address the phenomenon of violence against women in the Brazilian religious field. In this perspective, we sought to identify the historical- religious roots that served and serve as a structuring and legitimizing element of the so- called symbolic violence. The analysis of this work emerged from the sociological reading of the current Brazilian reality and sought to investigate, from some historical clippings, the process of consolidation and restructuring of symbolic violence in today’s society with regard to gender relations and the respective social roles of men. and women in contemporary society. The text seeks to demonstrate the important role that religion, in this specific case, Christianity, played in maintaining a patriarchal vision that still results in the marginalization and suppression of women in the social context. In this sense, we see Christianity as one of the main vehicles for promoting inequality between men and women.